MODEL MANAJEMEN RANTAI PASOK INDUSTRI PERIKANAN TANGKAP BERKELANJUTAN DI PROPINSI MALUKU (The Ideal Model of Supply Chain Management of Sustainability Industrial Capture fisheries in Maluku Province) - Siti Chairiyah Batubara; M. Syamsul Maarif; . Marimin; Hari Eko Irianto (Bogor Agricultural University, 2017)
ABSTRACTDesigning and managing Industrial capture fisheries Supply Chain is complex and its faces socially bound uncertainties such as poor collaboration, communication and information sharing. Such complexity cannot be reduced through quantitative supply chain design and management techniques.Â The aim of this study was design an industrial capture fisheries supply chain in Maluku Province using Soft System Methodology. Multi Dimensional Scaling (MDS)and SCOR was applied in analyzing situational conditions related to the sustainability and performance of industrial capture fisheries. Analysis on capture fisheries shows in less sustainable category (43.91)and Â the performance of both fishermen and company indicate an excellent and good grade. SSM analysis generated root definitions: Ministry of Marine Fisheries, Department of Marine, regional institution and stakeholder of the supply chain (O) realize the sustainable fishing industry and implementation of reliable activities in the fisheries sector and competitive globally (W) which integrates all the units along supply chain and coordinate the flow of materials, information and finance ranging from such aspects : production, downstream industries (handling and processing), up to marketing (T) of the Fishermen, industries processing (C) on the entire supply chain throughÂ effective and efficient mechanism (E) as well as coordination both center and regional institution (A) related to quality and standardization of fishery products, distribution, infrastructure, data and information on fisheries (T)